2015
DOI: 10.1590/01000683rbcs20140428
|View full text |Cite
|
Sign up to set email alerts
|

Revolvimento Ocasional e Calagem em Latossolo Muito Argiloso em Sistema Plantio Direto Consolidado

Abstract: ResumoA ocorrência de concentração de nutrientes e compactação superficial tem sido relatada após longo tempo de implantação do sistema plantio direto. o objetivo deste estudo foi avaliar os atributos químicos, a densidade do solo e a produtividade das culturas subsequentes a uma única intervenção mecânica complementada com calagem de um latossolo vermelho Distroférrico textura muito argilosa conduzido em sistema plantio direto há 17 anos ininterruptos, em Pato Branco, no sudoeste do Paraná. o delineamento exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Surface applications and limestone incorporations in the soil after 9 and 12 years of NTS (Ciotta et al, 2004), and after 11, 12, and 13 years (Wortmann et al, 2010), did not result in differences in the soil organic C content. Fidalski et al (2015) did no report differences between treatments for the organic C content in the superficial layer of a 17-year-old NTS, after six months of superficial or incorporated applications of limestone, but 11% increase of organic C content at 0.1 to 0.2 m soil depths. Therefore, it is possible that N fertilization levels, occasional soil tillage, and liming, interact significantly in a consolidated NTS, with consequences on wheat and corn yields and on soil chemical attributes.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Surface applications and limestone incorporations in the soil after 9 and 12 years of NTS (Ciotta et al, 2004), and after 11, 12, and 13 years (Wortmann et al, 2010), did not result in differences in the soil organic C content. Fidalski et al (2015) did no report differences between treatments for the organic C content in the superficial layer of a 17-year-old NTS, after six months of superficial or incorporated applications of limestone, but 11% increase of organic C content at 0.1 to 0.2 m soil depths. Therefore, it is possible that N fertilization levels, occasional soil tillage, and liming, interact significantly in a consolidated NTS, with consequences on wheat and corn yields and on soil chemical attributes.…”
Section: Introductionmentioning
confidence: 72%
“…Spacing at 3.5 m dividing two blocks on each side was used to improve feasibility and minimize the transit of machinery in the plots. The immediate effects of treatments with soil tillage and liming for corn (2009/2010), black oats (2010), and soybean (2011/2012) crops were reported by Fidalski et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a consolidated no-till cropping system Fidalski et al (2015) observed that liming incorporated into about 20 cm deep of the limestone with plow and harrow, had not exhibited any advantage in relation with surface liming (zero cm incorporation). Yagi et al (2014) observed that the soil limestone incorporation reduced the carbon frameworks of macro-aggregates in the layer of 0 to 0.10 m and concluded that surface liming is essential for the maintenance or even enhancement of carbon stocks in the soil.…”
Section: Introductionmentioning
confidence: 94%